An advanced multi-criteria evaluation model of the rational building energy performance - Migilinskas, Darius; Balionis, Evaldas; Dziugaite-Tumeniene, Rasa; Siupsinskas, Giedrius (Journal of Civil Engineering and Management, 2016)
Different optimization methods generate a large variety of solutions that are suitable for achieving the sets of chosen objectives. The selection of appropriate design variables and objective functions are essential elements in the optimization process. However, the existing methodologies seem to be too complicated and designers seek to use simpli-fied methods in order to evaluate the overall performance of the buildings. The advancement of information technology enables the use of Building Information Modelling and energy simulation tools for the integrated building design in an early stage. Thus, this article introduces a new evaluation method for analysis of the effective solution of the building performance and aims at determining the influence of a complex criteria (construction duration, construction cost, annual bill-based costs, annual primary energy demand, annual CO2 emissions of energy use, CO2 emissions of construction materials and works, thermal comfort) for the final decision making. The findings of the article have confirmed that the high level of the building energy efficiency is not directly proportional to the overall investments, i.e. additional invest-ments do not bring benefits from economic and environmental points of view.